Decomposition of Carbon Dioxide Gas Observation Using Optical Emission Spectroscopy Technique - Daniel Faris, Muhammad Daniel Faris Bin Dzulkarnain; Mohamed Ali, Riyaz Ahmad; Saidon, Nur Aqilah (Evolution in Electrical and Electronic Engineering, 2025)
Carbon dioxide (CO2) is a key component for the main atmospheric and industrial processes but it may cause a harm to the environment seriously if released excessively to the air. Optical emission spectroscopy (OES) is a non-intrusive and widely used technique for analyzing plasma generated light to detect and identify gaseous species including CO2. This paper focuses on the observation and decomposition of gas CO2 using OES aimed at isolating and interpreting the characteristics emission lines of CO2 and its dissociation byproducts. In this study, we use RIE system as a main optical emission experiment for gas CO2. To find the reading intensity in plasma chamber of RIE system, we use 2 software tools which are spectrasuite as a main platform to find reading gas intensity and originlab as a plot graph for comparison between different voltage and different working pressure. During the experiment, gas at different voltages such as 50 V, 100 V, 150 V, 200 V, 250 V, 300 V and 350 V and different working pressure such as 50 milliTorr, 100 milliTorr, 150 milliTorr and 200milliTorr, were being set. The findings from this study shows that at all working pressure and wavelength values, the input power is directly proportional to the produced gas intensity. Moreover, the use of OES combined with spectral decomposition proves to be an effective tool for the precise analysis of complex gas mixtures. This research lays the groundworks for future innovations in gas sensing technologies and emission control strategies involving CO2.